Transcriptomic Analysis of Radish (Raphanus sativus L.) Spontaneous Tumor - Alexander Tkachenko (Plants, 2021)
Spontaneous tumors can develop in different organs of various plant species without any pathogen infection and, as a rule, appear in plants with a certain genotype: Mutants, interspecific hybrids, etc. In particular, among the inbred lines of radish (Raphanus sativus L.), lines that form spontaneous tumors on the taproot during the flowering period were obtained many years ago. In this work, we analyzed the differential gene expression in the spontaneous tumors of radish versus the lateral roots using the RNA-seq method. Data were obtained indicating the increased expression of genes associated with cell division and growth (especially genes that regulate G2-M transition and cytokinesis) in the spontaneous tumor. Among genes downregulated in the tumor tissue, genes participating in the response to stress and wounding, mainly involved in the biosynthesis of jasmonic acid and glucosinolates, were enriched. Our data will help elucidate the mechanisms of spontaneous tumor development in higher plants.